Formation of complexes consisting of impurity Mn atoms and group VI elements in the crystal lattice of silicon - Ismailov, K.А.; Iliev, X.M.; Tursunov, M.O.; Ismaylov, B.K. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2021)
The formation of complexes of impurity Mn atoms with group VI impurities (S, Se, Te) in the silicon crystal lattice has been studied. It has been experimentally found that the formation of electrically neutral molecules with an ionic-covalent bond between Mn atoms and group VI elements takes place, which possibly leads to the formation of new Si₂BVI ⁺⁺Mn binary unit cells in the silicon crystal lattice. It has been shown that in the samples Si⟨S, Mn⟩, Si⟨Se, Mn⟩, and Si⟨Te, Mn⟩, intense complex formation occurs at 1100, 820, and 650 °C, respectively. Досліджено формування комплексів домішкових атомів Mn з домішковими атомами елементів VI групи (S, Se, Te) у кристалічній решітці кремнію. Експериментально виявлено, що має місце утворення електронейтральних молекул з іонно-ковалентним зв’язком між атомами Mn та елементами VI групи, що, можливо, призводить до формування нових бінарних елементарних комірок Si₂BVI ⁺⁺Mn у кристалічній решітці кремнію. Показано, що в зразках Si⟨S, Mn⟩, Si⟨Se, Mn⟩ та Si⟨Te, Mn⟩ відбувається інтенсивне комплексоутворення при температурах 1100, 820 та 650 °C відповідно.